Compostagem de lodo séptico e resíduos agrícolas em diferentes sistemas de aeração - Nascimento, Bruno Lucio Meneses (2017)
Treatment and final disposal of solid urban waste have always been a concern to governmental and non-governmental organizations related to the environmental sanitation area. With the publication of the law number 12305/2010 this concern has increased, as there is a target to reduce organic solid waste shipment to landfills. Thus, composting has been gaining ground in the national scenario once this technic can treat a large part of organic solid waste, hence improving its quality and giving it the possibility of being reused in agriculture, contributing to reduce the amount of this type of residue disposal in landfills. For this reason, our aim was to verify the final quality of the dewatered septic waste, cow manure and poultry litter composted with pruning from trees, and additionally to study the effect of different aeration systems during the process. Statistical scheme adopted was based on a factorial 2 X 3 X 5, with two aeration systems (forced aeration using aerogenerators and mechanic aeration using tractors), three types of residues (septic sludge, cow manure and poultry litter) and five composting periods (0, 30, 60, 90 and 120 days) being evaluated with three replicates. This study demonstrated that composting is an ecological solution to be implemented in the cities and mechanical aeration system was the best technique to obtain a higher quality compost. Based on the results found, septic sludge, cow manure and poultry litter are residues that enhance plant germination and growth. Regarding the microbiological quality, septic sludge and cow manure were free of any contamination after 120 days of composting. Mantis, Voultsa, and Samara (2005) classify solid waste regarding its ecotoxicity in four classes. In this work, cow manure and septic sludge belong to class 1 and do not have significant ecotoxicity, while poultry litter belongs to class 2 and has significant ecotoxicity. Substrate 2 made of cow manure and septic sludge and substrate 4 made of septic sludge and poultry litter provided higher growth and development in seedlings of Golden Trumpet Tree and Cedar. The crushed coconut, used as structurant, performed better as structurant when compared to tree pruning.